Ugody w unijnym i amerykańskim prawie konkurencji - Maziarz, Aleksander (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article analyzes the provisions on settlements in EU and US competition law. It focuses primarily on determining what conditions should be met for the company to be able to use this form of termination of antimonopoly proceedings. The article also examines whether participation in a settlement procedure is available to any potential company that has infringed competition law and whether there are sufficient incentives for companies to induce them to participate in such a procedure. The juxtaposition of solutions adopted in the EU and the USA made it possible to identify elements of a model solution for settlements in competition law.
Keywords: settlement; prohibition of competition-restricting agreements; antimonopoly proceedings